TEMBILAHAN COMMUNITY'S UNDERSTANDING OF CROWDFUNDING IN THE DEVELOPMENT OF THE DIGITAL ECONOMY: A QUALITATIVE STUDY - Alma Nadiya; Muhamad Muhlis Arya (Indragiri Research Center (ingreat), 2024)
The understanding of the Tembilahan community towards crowdfunding in the development of the digital economy is the focus of this study. The qualitative approach was used with in-depth interview, observation, and documentation techniques, and informants were selected purposively based on variations in age, education, and level of understanding of digital technology. The findings show that people's understanding of crowdfunding is influenced by digital literacy, financial literacy, experience using digital platforms, and local social and cultural contexts. This understanding shapes their perception of the benefits, risks, and role of crowdfunding in supporting local economic activities. These findings provide important insights for the development of digital literacy, crowdfunding information dissemination strategies, and policies that can encourage public participation in the digital economy.